Teacher Asisstance Thru The Digital Ready Teacher Program: Building The Nation With Technological Spirit At SDN 42 Ampenan - Ana Tri Rahmah; Lu’luul Haniifah; Seftina Ariyanti; Aulia Salsabila Zain; Prayogi Dwina Angga (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The digitall gap in SDN 42 Ampenan is a very important issue, students are already familiar with technology, while teachers are still using conventional methods due to age and time constraints. The program is about improving teachers’ digital skills. The service method applies four stages (identification, planning, implementation, evaluation) through participatory mentoring and hands-on training methods. This was done by three interactive sessions that introduced digital LKPD, 3D media, and AI. The mentoring results showed that hands-on practice had successfully broken through the resistance of teachers to technology. This training has hugely increased teachers’ motivation, confidence and practical understanding on how to integrate digital platforms in learning. This program has shown results and can be a replicable model for digital literacy in elementary schools.